2018
DOI: 10.1017/s1751731117001604
|View full text |Cite
|
Sign up to set email alerts
|

Grape pomace improves performance, antioxidant status, fecal microbiota and meat quality of piglets

Abstract: In the present study, grape pomace (GP) was used as feed additive in the diet of weaned piglets in order to develop innovative feedstuffs and to investigate their potential beneficial effects on welfare, productivity and meat quality. For examining the antioxidant capacity of the experimental feeds, 24 piglets of 20 days old were assigned to two experimental groups receiving standard or experimental diet for 30 days. Blood and tissues collections were performed at four different time-points, 2, 20, 35 and 50 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
71
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 29 publications
(40 reference statements)
7
71
1
8
Order By: Relevance
“…However, at 42 and 70 days of age, a slight decrease in TBARS and protein carbonyls was observed. In another study by our research group, we also reported that diet enriched in polyphenols from GP reduced the n-6/n-3 ratio and improved the meat fatty acid profile in growing piglets (13). In a recent study, Muíño et al (38) showed that inclusion of another winery by-product (red wine extract) in the diet also reduced the n-6/n-3 ratio of lamb meat.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…However, at 42 and 70 days of age, a slight decrease in TBARS and protein carbonyls was observed. In another study by our research group, we also reported that diet enriched in polyphenols from GP reduced the n-6/n-3 ratio and improved the meat fatty acid profile in growing piglets (13). In a recent study, Muíño et al (38) showed that inclusion of another winery by-product (red wine extract) in the diet also reduced the n-6/n-3 ratio of lamb meat.…”
mentioning
confidence: 62%
“…Recently, researchers have demonstrated the possibility of developing meat products with potential health benefits by introducing bioactive compounds with antioxidant properties into feedstuffs for animals (4,5). Our research group has also performed in vivo studies showing that by-products rich in polyphenols, generated from olive oil and the wine industry, improved antioxidant capacity, meat quality and welfare of productive animals, such as chickens, pigs and lambs (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Also, the final encapsulated powder of sample 3 had the highest content of total polyphenols, as well total polysaccharides, (followed by sample 2, which had the second-best prebiotic effect), to which the comparatively better prebiotic activity could be attributed to. In fact, other studies have also shown that plant polyphenols can act (at low concentrations) as stimulants of LAB or probiotic bacteria in food (e.g., yogurt) [55,56] or in vivo [57]. Kafantaris et al [57] reported that, when piglets were treated with grape pomace polyphenols, they had significantly lower levels of Enterobacteriaceae in their feces, and significantly increased levels of Bifidobacterium and Lactobacillus spp.…”
Section: Population (Log Cfu/ml) During Incubation In Simulated Gastricmentioning
confidence: 99%
“…In fact, other studies have also shown that plant polyphenols can act (at low concentrations) as stimulants of LAB or probiotic bacteria in food (e.g., yogurt) [55,56] or in vivo [57]. Kafantaris et al [57] reported that, when piglets were treated with grape pomace polyphenols, they had significantly lower levels of Enterobacteriaceae in their feces, and significantly increased levels of Bifidobacterium and Lactobacillus spp. In others studies conducted on rats [58] and humans [59], proanthocyanidin-rich extracts from grape seeds showed prophylactic effects against chemotherapy-induced intestinal injury (mucositis) [58] and significantly increased the number of Bifidobacteria (by 0.5 log cfu/g of feces on average), while inhibiting other groups such as Enterobacteriacae (0.8 log cfu/g of feces on average) [59].…”
Section: Population (Log Cfu/ml) During Incubation In Simulated Gastricmentioning
confidence: 99%
“…The higher value of both FRAP and ABTS assays compared with CON suggests a clear antioxidant capacity of GM, at tested dose. The antioxidant capacity of grape by‐products included in the diet has been previously observed in ruminants (Kafantaris et al, ) and monogastric (Brenes et al, ; Kafantaris et al, ). This effect is probably related to the high content of proanthocyanidins in GM, mainly composed of catechin, gallic acid and anthocyanin glucosides (Nudda et al, ).…”
Section: Discussionmentioning
confidence: 75%